Presentation of Body Sway Sensation Considering the Distinction Between Self-Motion and Environmental Motion Induced by Alternating Vibrations to Antagonistic Tendons in the Ankles - Eifu Narita; Keigo Ushiyama; Izumi Mizoguchi; Hiroyuki Kajimoto (IEEE Access)
In virtual reality (VR) environments and immersive content, the use of kinesthetic illusions has garnered attention as a simple yet effective method to present whole-body motion sensations, such as body sway and tilt. This study proposes a technique to present sensations of whole-body sway by alternately vibrating the antagonistic muscles of the ankle and manipulating the switching speed (frequency) of these vibrations to induce the interpretation of the sway as either “the body is moving” or “the environment (ground) is moving.” To validate the effectiveness of this method, three experiments were conducted. In Experiment 1, we investigated the effect of the switching frequency on the interpretation of sway. The results revealed a tendency for low frequencies to be interpreted as “self-sway” and high frequencies as “environmental sway.” In Experiment 2, we examined the influence of shifting the center of pressure (CoP) in the anterior-posterior direction on sway interpretation. While the CoP position had minimal impact on sway interpretation, the results suggested that the strength of the illusion slightly decreased under high-frequency conditions when the CoP was biased towards the toes or heels. In Experiment 3, we presented visual stimuli of sway with various phase delays and assessed whether the match between the visual stimuli and the vibration-induced sway illusion changed. Although phase delays did not strongly affect the matching scores, the results indicated that visual stimuli might contribute to the interpretation of the illusion. These findings demonstrate the potential of a technique that adjusts the switching frequency of vibrations to differentiate between “self-sway” and “environmental sway” in VR and immersive content. Furthermore, the limited impact of integrating visual stimuli on the interpretation and strength of the illusion suggests that highly immersive and convincing experiences can be designed even without strict synchronization between visual and tactile stimuli.